2017
DOI: 10.1002/term.2607
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells seeded on a human amniotic membrane improve liver regeneration and mouse survival after extended hepatectomy

Abstract: Liver failure remains the leading cause of post-operative mortality after hepatectomy. This study investigated the effect of treatment with allogenic mesenchymal stem cells (MSCs) on survival and liver regeneration 48 hr and 7 days after 80% hepatectomy in C57Bl/6 mice. To optimize their biodistribution, MSCs were grown on acellular human amniotic membranes (HAM) and applied as a patch on the remnant liver. This approach was compared with MSC infusion and HAM patch alone. Hepatectomized mice without any treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Previous studies have suggested potential application of MSCs in the treatment of injured tissues [ 31 , 32 ]. However, there are limitations of such applications because of poor conditions near the application area from pathophysiological conditions including high ROS levels, inflammation, and apoptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested potential application of MSCs in the treatment of injured tissues [ 31 , 32 ]. However, there are limitations of such applications because of poor conditions near the application area from pathophysiological conditions including high ROS levels, inflammation, and apoptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steatosis was evaluated as follows: (a) the percentage of steatotic cells relative to the total number of cells per section by manual counting all cells containing one or more lipid droplets, and (b) the number of lipid droplets in hepatocytes was used to define steatosis as mild (one droplet/cell), moderate (few droplets/cells), or severe (numerous droplets filling the cytoplasm). 17 Histological evaluation was conducted by two blinded observers (A.A. and S.W).…”
Section: Histological Analysismentioning
confidence: 99%
“…The administration of multipotent cells, for example, mesenchymal stem cells (MSC) and hematopoietic stem cells (HSC), and their potential for modulating vascular inflammation and organ regeneration has caught the attention of various groups during the last years. Others and we have gained broad experiences early with multipotent stem cells in different experimental liver failure models 12,13,[15][16][17][18][19] and in clinical settings. [20][21][22] Although, immunomodulatory and regenerative capacities of multipotent stem cells have been confirmed in different experimental settings, the administration of MSC to investigate liver regeneration in a clinical setting has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix derived from human amniotic membrane has various components and bioactivities, which allow such matrix to be widely applied in corneal transplantation, retinal regeneration, liver regeneration, and wound healing. [21][22][23][24] Due to its anti-inflammatory effects, anti-fibrotic effect, and angiogenic potentials, [25][26][27][28] we postulate that materials derived from hAM could beneficial for restoring cardiac function following MI.…”
Section: Introductionmentioning
confidence: 99%